Integrism towards contemporary Christian religious education and teaching of the Second Vatican Council - FIGIEL, DOMINIK (Journal of Education Culture and Society, 2020)
Intercultural education as a result of social changes has allowed expansion of dialogue boundaries. As a result, a new approach to religious education has been formed. First of all, it was the emergence of streams and processes affecting the perception, meaning and place of Christian religion in the contemporary world. This was connected with the Second Vatican Council and the effects of the decisions concerning religion. The new slogans propagated by a modernist environment such as religious freedom or ecumenism, led to the opposition in traditionalist circles. The most radical attitude was presented by The Saint Pius X Fraternity and its founder Marcel Lefebvre. All views, attitudes and actions directed towards the objec-tion to modernist changes are called integrism, and its representatives are integrists.